Analisis Keterampilan Pengelolaan Kelas dalam Meningkatkan Motivasi Belajar Siswa Kelas IV SDN 1 Sesean - Sefrin Siang Tangkearung; Novalia Sulastri (LPPM UKI Toraja, 2022)
The purpose of this study was to determine classroom management skills in increasing students' learning motivation. This research is a qualitative research with a descriptive approach.This study aims to describe classroom management skills in increasing students' learning motivation. The data sources of this research are teachers and fourth grade students who use the interview instrument with a structured interview list. The results of this study indicate that the teacher has been able to manage the class well, the classroom management carried out by the teacher is like showing a responsive attitude, focusing the attention of the group, namely the teacher asks students to pay attention to the explanation of the material given and then asks all groups if there are those who do not understand then the teacher re-explaining the given task, giving clear instructions, admonishing students well by speaking firmly and clearly without saying rudely or pinching or hitting students, providing reinforcement, namely the teacher gives praise to each student who answers the wrong or correct question so that keep the spirit in learning.From classroom management by teachers, it can also generate student learning motivation because a good relationship between students and teachers that is well established can increase student learning motivation where students do not easily give up in doing assignments and the role of teachers who can arouse students' enthusiasm in learning and teachers who can create a pleasant classroom atmosphere.